2018
DOI: 10.1002/app.46754
|View full text |Cite
|
Sign up to set email alerts
|

Development of starch‐furcellaran‐gelatin films containing tea tree essential oil

Abstract: Tea tree essential oil (TEO) was added in different concentrations (2%, 4%, and 6%) to starch/furcellaran/gelatin (S/F/G) films. Film solubility of S/F/G film significantly decreased when containing 6% TEO (P ≤ 0.05). Referring to the control sample (without TEO), water content decreased with increasing concentration of oil. Films with 4% and 6% TEO exhibited a significant decrease (P ≤ 0.05) in tensile strength, and Young's modulus. The amounts of TEO had no significant on the elongation at break (P ≤ 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Studies on furcellaran‐starch‐gelatin films with 2% of TTO show a peak at 1453 cm −1 band, related to the interaction between oil and matrix. However, only films with 6% of TTO exhibit peaks related to the stretching vibrations of CO groups present in the TTO . Although there are few differences between the peaks, it is important to mention that they were enough to change the film FTIR spectrum.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Studies on furcellaran‐starch‐gelatin films with 2% of TTO show a peak at 1453 cm −1 band, related to the interaction between oil and matrix. However, only films with 6% of TTO exhibit peaks related to the stretching vibrations of CO groups present in the TTO . Although there are few differences between the peaks, it is important to mention that they were enough to change the film FTIR spectrum.…”
Section: Resultssupporting
confidence: 90%
“…For example, Medina‐Jaramillo et al found water solubility for cassava starch–glycerol films incorporated with extracts of green tea ranged from 28 to 30% . The incorporation of 6% of TTO in a cassava starch‐gelatin‐furcellaran‐based films results in a 42% of solubility, a value 2.5 times higher than the solubilities of the present work …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tea tree is an essential oil of Melaleuca alternifolia, and it is a complex mixture of terpen hydrocarbons and tertiary alcohols. Its main components are terpinen‐4‐ol and 1.8‐cineole (Jamróz et al, 2018 ). The copaíba presents different amounts of substances in the oil composition.…”
Section: Introductionmentioning
confidence: 99%
“…A significantly lower level of malonaldehyde was observed in the blood of animals fed with CSGH encapsulated in microcapsules compared with animals fed the CSGH diet not subjected to microencapsulation. According to Jamróz et al [39], furcellaran has naturally-occurring polyphenols with antioxidant activity. It has been proven that polyphenols derived from marine algae have the ability to suppress the increase in lipid peroxidation levels in laboratory animal organisms [40].…”
Section: Resultsmentioning
confidence: 99%